Spatial Analysis of the Concentration of Knowledge-Based Firms in Iran - Najmoddin Yazdi; Mahdi Fateh-rad; Jamal Kadkhodapour; Siamak Tahmasbi (برنامه ریزی فضایی)
AbstractThe significance of knowledge-based firms in transitioning to a knowledge-based economy and fostering regional development has become increasingly evident to researchers and policymakers. Over the past decade, Iran has witnessed remarkable growth in knowledge-based firms supported by various financial and non-financial incentives from the government. However, research has largely overlooked the spatial patterns of distribution and concentration of these firms at both national and sub-national levels, as well as the factors driving their concentration in specific regions. Understanding these spatial patterns and centralizing forces is crucial for policymakers aiming to design effective strategies for the development of peripheral regions and establishment of a regional innovation system. This study aimed to analyze the spatial concentration of knowledge-based firms and the factors influencing this process. To measure spatial concentration, we employed global Moran’s I and Getis-Ord Gi* statistics, while Ordinary Least Squares (OLS) regression was used to identify determinants. The results indicated that the distribution of knowledge-based firms was predominantly concentrated in metropolitan areas with no significant clusters forming in marginal regions, which had not reaped the associated benefits. The centralizing forces of economies of scale and urbanization had played a pivotal role in this spatial concentration. Additionally, our findings revealed a low degree of specialization among knowledge-based firms. Finally, we presented policy implications aimed at providing incentives for the geographical redistribution of knowledge-based firms in less developed and peripheral regions, while also promoting regional specialization. Keywords: Knowledge-Based Firms, Spatial Concentration; Urbanization Economies, Economies of Scale, New Economic Geography. IntroductionKnowledge is a fundamental driver of economic growth and a crucial component in enhancing competitiveness among countries and regions. In the shift toward a knowledge-based economy, knowledge-based firms play a vital role and have garnered increasing attention from both academic literature and policymakers. Industries and companies tend to cluster in specific locations, a phenomenon supported by extensive global evidence. The study of the geographic concentration of economic activities has a long history and has gained significant interest in recent years. Geographic concentration is essential for regional development as it enhances efficiency and fosters innovation among firms. However, some studies have also highlighted its negative aspects, such as the exacerbation of regional inequality. The self-reinforcing nature of spatial concentration creates favorable economic conditions for certain areas while leaving others relatively underdeveloped. Moreover, in regions where companies, industries, and populations are concentrated, negative externalities can arise, including congestion costs, pollution, high land rents, and disruptions to essential services, such as healthcare, education, and urban infrastructure. In Iran, the number of knowledge-based firms has grown significantly over the past decade with over 8,400 firms now registered. Given the importance of these firms in regional development, it is crucial to examine their geographic distribution patterns and concentration. A comprehensive understanding of the spatial distribution of knowledge-based firms is essential for policymakers seeking to implement effective innovation and regional policies at local, regional, and national levels. This research aimed to analyze the spatial distribution and concentration of knowledge-based firms in Iran and investigate the factors that contributed to this concentration. Materials & MethodsThis research was classified as applied and exploratory-confirmatory in nature, employing various methods to achieve its objectives. To measure the spatial concentration of knowledge-based firms, we utilized global Moran's I and local Moran's I statistics, along with Ordinary Least Squares (OLS) regression, to model the relationships between determining factors and spatial concentration. Data on knowledge-based firms were obtained from the website of the Vice Presidency for Technology and the Knowledge-Based Economy, while the data related to the independent variables were sourced from the annual publications of the Iranian Statistics Center. Research FindingsThe spatial distribution of knowledge-based companies was analyzed across several technology fields: 1) electricity and electronics, photonics, telecommunications, and automation systems; 2) information and communication technology and software; 3) advanced machinery and equipment; 4) advanced medicine, diagnostic, and treatment products; 5) commercialization services; 6) biotechnology, agriculture, and food industries; 7) cultural industries, creative industries, and human sciences; 8) medical devices, necessities, and equipment; and 9) advanced materials and products based on chemical technologies. The findings indicated a significant increase in the number of companies. In terms of technology sectors, the largest concentrations were found in electricity and electronics (1,822 companies), information technology (1,777 companies), and advanced machinery and equipment (1,721 companies). However, the distribution of knowledge-based firms was uneven, primarily concentrated in specific regions, particularly in the North-West (East Azerbaijan) and North-East (Khorasan-Razavi) areas. Notably, over half of the knowledge-based firms (51.5%) were located in Tehran Province followed by Isfahan (9.3%) and Razavi Khorasan (5.3%). This distribution aligned with the presence of metropolitan areas (cities with populations exceeding one million). Additionally, the degree of specialization among companies was assessed using the Herfindahl index, revealing an overall low level of specialization. In contrast, the southern and southeastern provinces demonstrated greater diversity in their knowledge-based industries.The Moran's I index for the total number of knowledge-based firms, as well as for specific fields, such as electricity and electronics, advanced machinery and equipment, advanced materials and technology-based products, and medical devices and equipment, yielded positive values. With 999 random permutations, these results were significant at a level of less than 0.005. Thus, we rejected the assumption of randomness in the distribution of these firms and confirmed the presence of clustering, indicating spatial dependence in the data distribution. In contrast, Moran's I values for firms in information and communication technology, commercialization services, and biotechnology and agriculture were not significant, suggesting a lack of spatial autocorrelation. To identify local clusters, we employed the Getis-Ord statistic, which revealed a substantial cluster of high concentrations of knowledge-based firms extending from the northern region (Mazandaran Province) to the central areas (Isfahan Province). Conversely, clusters of low concentrations were observed in Hormozgan and Ilam provinces.We utilized the OLS regression model to analyze the conditions and factors influencing the concentration of knowledge-based companies in specific regions. The results indicated that the independent variables accounted for 36% of the variance. Among these variables, the rate of industrialization and logarithm of the population in provincial capitals exhibited a positive and significant relationship with the concentration of knowledge-based firms. In contrast, the percentage of individuals with higher education and GDP share of provinces did not show significant correlations. Higher rates of industrialization and larger populations in provincial capitals were associated with greater concentrations of knowledge-based companies. This suggested that firms were more likely to establish themselves in areas with a robust industrial presence, which provided the necessary infrastructure, resources, and business ecosystem to support innovation and technological advancement. Additionally, larger urban populations typically offered more potential customers, a larger talent pool for skilled labor, and better access to services and amenities, all of which were attractive factors for knowledge-based companies. Discussion of Results & ConclusionUtilizing spatial data allowed us to circumvent the limitations associated with classical statistical methods for measuring spatial concentration. The findings indicated that knowledge-based firms exhibited autocorrelation and were concentrated in clusters within specific regions. However, the overall degree of specialization among these firms remained low. Clustering served as a strategy to leverage the positive externalities associated with spatial concentration. The concentration of knowledge-based firms was not attributable to a single factor; rather, a combination of centripetal forces drove this phenomenon. In this study, we focused on several of these centripetal forces with urbanization economies and economies of scale identified as the most significant contributors to the concentration of firms in particular areas. The results had important implications for policies aimed at